Multi - sensory integration for a digital earth nervous system - Ostermann, Frank (2020)
The amount of geospatial data is increasing, but interoperability issues hinder integrated discovery, view and analysis. This paper suggests an illustrative and extensible solution to some of the underlying challenges, by extending a previously suggested Digital Earth Nervous System with multi-sensory integration capacities. In doing so, it proposes the combination of multiple ways of sensing our environment with a memory for storing relevant data sets and integration methods for extracting valuable information out of the rich inputs. Potential building blocks for the implementation of such an advanced nervous system are sketched and briefly analysed. The paper stimulates more detailed considerations by concluding with challenges for future research and requesting a multidisciplinary development approach – including computer sciences, environmental sciences, cognitive and neurosciences, as well as engineering